Assessing the feasibility of forest plantation of native species: A case study of Agathis dammara and Eusideroxylon zwageri in Balikpapan, East Kalimantan, Indonesia - Budi Setiawan; Abubakar M. Lahjie; Syahrir Yusuf; Yosep Ruslim (Society for Indonesian Biodiversity, 2019)
Abstract. Setiawan B, Lahjie AM, Yusuf S, Ruslim Y. 2019. Assessing the feasibility of forest plantation of native species: A case study of Agathis dammara and Eusideroxylon zwageri in Balikpapan, East Kalimantan, Indonesia. Biodiversitas 20: 2453-2461. Plantation forest using native species is very important effort to support biodiversity conservation. Still, analysis on its feasibility is needed to guarantee the sustainable forest management. The research aims were to assess the feasibility of plantation forestry of Agathis dammara and Eusideroxylon zwageri based on production models and financial simulation of stands management. The production models were developed based on plantation forests in Balikpapan, East Kalimantan, Indonesia. Using these plantation we developed models to estimate tree volume, total volume per hectare, Mean Annual Volume Increment (MAI) and Current Annual Increment (CAI) for each species. Financial analyses were carried out to assess the Pay Back Period (PBP), Net Present Value (NPV), Net Benefit/Cost (B/C) Ratio, Internal Rate of Return (IRR) and Equivalent Annual Annuity (EAA). The results of production model showed that A. dammara stands would reach optimum production at the age of 25 years while that of E. zwageri at the age of 150 years. A. dammara stands produce higher MAI of 15.67 m3ha-1 year-1 and total volume of 383.72 m3ha-1 than E. zwageri with MAI 1.89 m3ha-1 year-1 and total volume of 282.78 m3ha-1. The result of financial analysis showed that A. dammara plantation had the IRR higher than the Minimum Acceptable Rate (MAR) and the Net B/C Ratio of higher than 1, while E. zwageri had the Net B/C Ratio of lower than 1. A. dammara plantation also had a positive NPV value of IDR 78,699,974 while E. zwageri plantation had a negative NPV value of IDR 91,439,292. These results suggest that developing A. dammara plantation is more desirable than E. zwageri plantation.